Prognostic impact of blood transfusion in patients with metastatic non-small cell lung cancer receiving chemotherapy. (July 2019) - Sakin, Abdullah; Sahin, Suleyman; Yasar, Nurgul; Demir, Cumhur; Arici, Serdar; Geredeli, Caglayan; Cihan, Sener
Highlights: Blood Transfusion may cause various immune system dysfunctions, leading to immunosuppression. The advers effect of blood transfusions in cancer patients has been investigated in various cancer types. The knowledge on this issue has been under debate in lung cancer. Blood trasfusion is associated with earlier progression and shorter survival in Lung adenocancer. Abstract: Purpose: To investigate the prognostic effects of Allogeneic Blood Transfusion (ABT) in patients with metastatic Non-Small Cell Lung Cancer (NSCLC) receiving Chemotherapy (CT) in the first-line treatment, comparing untransfused patients to those receiving blood transfusion during treatment period or before treatment period. Methods: This was a retrospective study of 433 patients with metastatic NSCLC receiving CT in the first-line treatment. Patients were categorized into 3 groups according to the transfusion strategy as follows; group-U(Untransfused patients, n = 303), group-B(patients receiving transfusion Before treatment period, n = 43), and group-D(patients receiving transfusion During treatment period, n = 87). Results: There were 433 patients in the analysis, consisting of 388 (89.6%) males, with a median age of 60 years(range, 21–92). The median Overall Survival(mOS) according to the ABT was 14 months for group-U, 9 months for group-B, and 7 months for group-D (p < 0.001). In subgroup analysis, patients with squamous cell carcinoma subtype, mOS was 11 months for group-U, 12 months for group-B, and 9 month for group-D (p = 0.074) The corresponding mOS durations for adenocarcinoma subtype were 21 months, 7 months, and 6 months (p < 0.001). Performing ABT during treatment period was found to be a negative independent factor related to OS (HR 1.50 for progression-free survival, 95% CI 1.15–1.97, HR 1.36 for OS, 95% CI 1.04–1.80). Conclusion: Our results demonstrated that ABT was significantly associated with earlier progression and shorter survival in patients with metastatic NSCLC, especially in adenocarcinoma histology, hence suggesting that transfusion strategy in this group should remain limited, and its benefit should outweigh the risk of progression.